2020
DOI: 10.1038/s41598-020-64190-2
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Roles of US3 Protein in Cell-to-Cell Spread and Virion Nuclear Egress of Duck Plague Virus

Abstract: The duck plague virus (DPV) US3 protein, a homolog of the herpes simplex virus-1 (HSV-1) US3 protein that is reported to be critical for viral replication, has been minimally studied. Therefore, to investigate the function of the DPV US3 protein, we used scarless Red recombination technology based on an infectious bacterial artificial chromosome (BAC) containing the DPV Chinese virulent strain (CHv) genome and successfully constructed and rescued a US3-deleted mutant and the corresponding revertant virus (BAC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…A previous study verified that the US3 protein does not affect the production of viral genome copies ( Deng et al, 2020 ). As a kind of herpesvirus tegument protein, whether DPV UL11 influences viral replication remains to be explored.…”
Section: Resultsmentioning
confidence: 66%
“…A previous study verified that the US3 protein does not affect the production of viral genome copies ( Deng et al, 2020 ). As a kind of herpesvirus tegument protein, whether DPV UL11 influences viral replication remains to be explored.…”
Section: Resultsmentioning
confidence: 66%
“…Earlier studies showed that a mutant with a UL14 deletion generated small plaques after infection of HSV-1 cells ( Cunningham et al, 2000 ). Furthermore, previous studies on DPV indicated that duck plague virus glycoprotein I influenced cell-cell spread and that US3 had a similar function ( Deng et al., 2020 ; Liu et al., 2020 ). In our study, we found that the UL14 deletion mutant still produced smaller viral plaques and lower viral titers ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 95%
“…Multistep growth kinetics of the parental strain CHv-50, DPV CHv-gEΔET, and DPV CHv-gEΔCT deletion mutant viruses were performed as previously described with minor modifications ( 31 , 32 ). Briefly, DEFs cultured in 24-well cell culture plates were infected with a virus at an MOI of 0.01.…”
Section: Methodsmentioning
confidence: 99%